Identified Of Indicator And Material For Product Shelf Life Recorder Smart Label - Warsiki, Endang; Octaviasari, Riris (Department of Technology of Agricultural product (THP) Jambi University, 2017)
Shelf life is an important factor in determining the quality and safety of food for consumption. Refrigerator becomes an alternative in extending product shelf life. Shelf life is difficult to be identified if the product stored for too long. Smart label of Time Temperature Indicators (TTI) can record the product shelf life based on its storage time. In this research, identification of indicator and material for smart label development based on liquid diffusion in material was conducted. This study used several types of materials (Buffalo paper, HVS 80 gr, photo paper, concord, drawing paper and cardboard duplex), low viscosity indicators (board-marker ink, stamp, tubs, permanent tattoo and non-permanent tattoos) and high viscosity indicators (cooking oil, lubricant A and lubricant B). The initial phase was characterizations such as grammage, density, mass density and viscosity test aimed to determine the properties of indicators and materials. Identification was implemented by measuring the diffusion length of indicator in the material at 24, 48, 72 and 96 h in temperature of 30.15°C and 50°C for cooking oil, while 30.15°C and 5°C for oil A and B. The slope of diffusion length versus time is called by rate constant (k), where as the slope of ln k versus 1/T is called by activation energy (Ea). Best indicator and the material were selected based on their high value of Ea. Result showed that the ink was not be absorbed during storage due to its high volatility and low viscosity, while cooking oil, lubricant A and lubricant B have specific diffusion length during storage. These indicators and mediums were able to detect up to 4 days of shelf life during storage. Based on activation energy, the most suitable indicator for smart label was lubricant A. The best materials for this label development sequentially from low-to-high activation energy were Buffalo paper, duplex cartons, drawing paper, concord, HVS 80 g and photo paper.